2007
DOI: 10.1021/jp074013b
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Spectroscopic Properties of Dimethoxy-p-Phenylene-Ethynylene Oligomers:  Planarization of the Conjugated Backbone

Abstract: The optical spectra of the dimethoxy-p-phenylene-ethynylene oligomers (up to n ) 10) are calculated by DFT and TD-DFT methods. It is found that the conformational rotations around the cylindrical triple-bonded carbon links impact significantly the optical spectrum. The effective conjugation length (ECL) of the oligomer is obtained by extrapolating the HOMO-LUMO gap to infinite chain length with an alternative exponential function. The spectral shift is mainly dependent on the high π-conjugation segment of olig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 45 publications
3
54
0
Order By: Relevance
“…13,66 Regarding chromophore 5, conjugation among the triphenylamine core and three branches through CC do exist, but it is not as strong as that in chromophore 4 because of the small twisting barrier of the CC bond. 10,58 Therefore, in chromophore 5, for low-energy ICT states, triphenylamine core is more active, charge is partially distributed overall molecule, and the CDD distribution at each branch agrees with C 3h symmetry Frenkel exciton model expressions (see Table S2e states, triphenylamine core is not that active, charge redistribution is partially restricted, and the CDD distribution is slightly different from the expressions of an ideal C 3h symmetry Frenkel exciton model. The angle between transition dipole moments from the ground state to the low-energy ICT states and those from the ground state to the high-energy ICT states is estimated about ∼19.3°.…”
mentioning
confidence: 57%
“…13,66 Regarding chromophore 5, conjugation among the triphenylamine core and three branches through CC do exist, but it is not as strong as that in chromophore 4 because of the small twisting barrier of the CC bond. 10,58 Therefore, in chromophore 5, for low-energy ICT states, triphenylamine core is more active, charge is partially distributed overall molecule, and the CDD distribution at each branch agrees with C 3h symmetry Frenkel exciton model expressions (see Table S2e states, triphenylamine core is not that active, charge redistribution is partially restricted, and the CDD distribution is slightly different from the expressions of an ideal C 3h symmetry Frenkel exciton model. The angle between transition dipole moments from the ground state to the low-energy ICT states and those from the ground state to the high-energy ICT states is estimated about ∼19.3°.…”
mentioning
confidence: 57%
“…[27][28][29] A successful quantitative conversion of butadiynes in the polymer chain into heterocycles will introduce heteroatoms into the polymer backbone, thus red-shifting the polymer's photophysical properties.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the efficient oxidation of palladium by benzoquinone, the PPBs' randomness obtained from two alkynes is believed to improve the solubility and molecular weight of the block copolymers. 27 The same group also demonstrated that high molecular weight PPBs (up to ~124,000 g/mol) were synthesized by using bulky iptycene monomers, minimizing interchain stacking. 28 The rigid iptycene scaffolds are also known to minimize π-π stacking in solid films, preserving the photophysical properties suitable for ultrasensitive detection of chemicals.…”
Section: Interlocking) Williams Et Al Demonstrated Various Ppb Syntmentioning
confidence: 99%
See 2 more Smart Citations